Standardized microhaplotype databases and frameworks for assessing and mining crop genetic diversity - Dongyan Zhao; Meng Lin; Cristiane H. Taniguti; Alexander M. Sandercock; Shufen Chen; Ebrahiem Babiker; Nahla V. Bassil; E. Charles Brummer; Jose Roberto Camacho; Warren Chatwin; Shu-Yun Chen; Shaun J. Clare; et al. (Theoretical and Applied Genetics, 2026)
Keymessage Standardized microhaplotype databases for eight diverse crops enable multiallelic analyses, comparative genetics, and breeding decisions. Abstract Microhaplotypes are short genomic segments that contain multiple tightly linked variants, providing multi-allelic data that can enhance genetic resolution compared to traditional biallelic single nucleotide polymorphism (SNP) markers. Here, we present the creation and utilization of separate microhaplotype databases for eight crop species representing diverse genome sizes, ploidy levels, and breeding systems. We developed a standardized, species-agnostic pipeline for processing, filtering, and databasing microhaplotypes generated using the DArTag targeted genotyping platform. To enhance user accessibility, we developed a no-code, user-friendly application, HapApp, that uses an R Shiny front-end interface to allow breeders and researchers to add unique, standardized microhaplotype identities from raw DArTag reports and iteratively update the existing crop-specific database with the newly discovered microhaplotypes. Selected case studies with these databases highlight the operational advantages of microhaplotypes, especially for challenging, highly heterozygous, or polyploid species. They offer an informative alternative to traditional biallelic SNP analyses for resolving population structures and improving linkage map ordering. This integrated framework provides a reproducible and scalable foundation for managing and exploiting microhaplotype data in plant breeding and genetic research, enabling robust cross-project comparisons and facilitating trait discovery in both simple and complex crop genomes, while enabling comparative genomics and cross-species functional transfer that accelerates genetic gains across all crop species.

Prenatal and early postnatal lead exposure and later adulthood BMI: The Saint Louis baby tooth – Later life health study - Joyce J.Y. Lin; Ruby Hickman; Michael Leung; Justin Farmer; Ian W. Tang; Kaleigh McAlaine; Tracy Punshon; Brian P. Jackson; Felicitas B. Bidlack; Joseph J. Mangano; Marc G. Weisskopf (Environmental Research, 2026)

Cross-country differences in consumer acceptance and advocacy of novel food technologies - Brian Lin; Denise Conroy; Amy Errmann; Caixia Gan; Hugo Fahn (Food Quality and Preference, 2026)

Mechanistic characterization of insecticidal Shiva toxin interactions with Drosophila melanogaster nicotinic acetylcholine receptors - Kyle D. Schneider; Joseph Tourtois; Daniel Bertrand; Kumiko Kambara; Daniel Hulbert; Alexandra Haase; Sophia R. Kanniainen; Brian DeVree; Robert M. Kennedy; Lin Bao (Pesticide Biochemistry and Physiology, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Rapid Onset and Short Duration of TrenibotulinumtoxinE for Treatment of Moderate to Severe Glabellar Lines: Efficacy and Safety Results from a Phase 3 Study - Marion Moers-Carpi; Cheryl Burgess; Brian Biesman; Deirdre Hooper; Alexander Rivkin; Chung-Yi Chiang; Grace S. Park; Amy Weitzenfeld; Joan-En Chang-Lin (Toxicon, 2026)

Hyperspectral OCI/PACE observations of the Atlantic Sargassum - Lin Qi; Menghua Wang; Chuanmin Hu; Yuyuan Xie; Brian B. Barnes (Remote Sensing of Environment, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Modeling and verification of dynamic field ionization for laser-target interactions - Brandon M. Medina; Scott V. Luedtke; Lin Yin; Brian J. Albright (Computer Physics Communications, 2026)

Automated digital reconstruction of high-fidelity present-day geometries for segmental tunnel linings based on segmented point clouds - Wei Lin; Brian Sheil; Pin Zhang; Jiaqi Chang; Xiongyao Xie (Tunnelling and Underground Space Technology, 2025)

Pelagic Sargassum in the Florida Keys: assessment using high-resolution remote sensing - Sully Sullivan; Chuanmin Hu; Brian B. Barnes; Lin Qi (International Journal of Remote Sensing, 2025)

A Circular Economy Model of Sustainable Growth - Jhy -Yuan Shieh; Brian Chi-ang Lin; Jhy-Hwa Chen (Circular Economy and Sustainability, 2025)

Those floating materials in the northern Adriatic Sea: Observations from satellites - Madjid Hadjal; Brian B. Barnes; Lin Qi; Karlis Mikelsons; Menghua Wang; Chuanmin Hu (Science of The Total Environment, 2025)

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Monitoring pelagic Sargassum in the Atlantic Ocean from space: Principles and practices - Chuanmin Hu; Brian B. Barnes; Lin Qi; James F.R. Gower; Junnan Jiao; Yuyuan Xie (Harmful Algae, 2025)

Combustion of micron-sized iron particles in a drop tube reactor - Ruru Chen; Leon C. Thijs; Brian Brun Hansen; Weigang Lin; Hao Wu; Peter Glarborg; Aki Fujinawa; Xiaocheng Mi (Fuel, 2025)

Long-term trends in heat wave gaps for the New York City metropolitan area - Anthony Lin; Brian A. Colle (Urban Climate, 2025)

Temperature and carotid intima-medial thickness: The coronary artery risk development in young adults (CARDIA) study - Brian T. Joyce; Jie Yao; Yinan Zheng; Tao Gao; Drew Nannini; Shao Lin; Xin Li; Jaymie Meliker; Qianqian Song; David R. Jacobs; Donald Lloyd-Jones; Lifang Hou; et al. (Science of The Total Environment, 2024)

Deactivation of iron particles during combustion and reduction - Ruru Chen; Brian Brun Hansen; Weigang Lin; Hao Wu; Peter Glarborg (Fuel, 2024)

Unleashing the potential of waste: A supercharged high-performance 3D printing resin from discarded polylactic acid - Yu-Chung Chang; Lin Shao; Wangcheng Liu; Brian J. Bliss; Baoming Zhao; Zihui Zhao; Jinwen Zhang (Chemical Engineering Journal, 2024)

Seg2Tunnel: A hierarchical point cloud dataset and benchmarks for segmentation of segmental tunnel linings - Wei Lin; Brian Sheil; Pin Zhang; Biao Zhou; Cheng Wang; Xiongyao Xie (Tunnelling and Underground Space Technology, 2024)

To pool or not to pool data? Applying a generalized depletion model to assess American eel elver Anguilla rostrata fisheries from multiple rivers in Nova Scotia, Canada - Yu‐Jia Lin; Brian M. Jessop (Fisheries Management and Ecology, 2024)
Spatial scales are important for examining health of exploited fishery stocks and guiding management actions. However, information about the optimal spatial scale is still unclear for assessment of transit fisheries, such as elver fisheries of the American eel Anguilla rostrata . We applied a generalized depletion model to assess catch and effort data from three nearby rivers (within 50 km) to test the hypothesis that modeling on pooled and separate data from nearby rivers would give similar estimates of abundance and exploitation rate. Overall, pooling data from rivers within 50 km did not result in large differences (

Treatment of Moderate-to-Severe Glabellar Lines With RelabotulinumtoxinA, an Investigational Liquid Botulinum Toxin: Clinical Efficacy and Safety Results From the READY-1 Phase 3 Trial - Nowell Solish; Amir Moradi; Sachin Shridharani; Lisa Donofrio; Michael H Gold; Brian Biesman; Melissa Chiang; Rosalyn George; Kristel Polder; Rob Schwarcz; Xiaoming Lin; Sarah Coquis-Knezek (Toxicon, 2024)

Hemp fiber reinforced dual dynamic network vitrimer biocomposites with direct incorporation of amino silane - Mingen Fei; Wangcheng Liu; Lin Shao; Yiding Cao; Brian J. Bliss; Baoming Zhao; Jinwen Zhang (Chemical Engineering Journal, 2024)

Identification of a fundamental cryoinjury mechanism in MSCs and its mitigation through cell-cycle synchronization prior to freezing - Brian H. Johnstone; Dongsheng Gu; Chieh-Han Lin; Jianguang Du; Erik J. Woods (Cryobiology, 2023)

Measuring the effects of typhoon trajectories on dengue outbreaks in tropical regions of Taiwan: 1998–2019 - Brian Kao; Chia-Hsien Lin; Tzai-Hung Wen (International Journal of Biometeorology, 2023)

Nitrogen isotope enrichment predicts growth response of Pinus radiata in New Zealand to nitrogen fertiliser addition - Loretta G. Garrett; Yue Lin; Amanda L. Matson; Brian D. Strahm (Biology and Fertility of Soils, 2023)
The fertiliser growth response of planted forests can vary due to differences in site-specific factors like climate and soil fertility. We identified when forest stands responded to a standard, single application of nitrogen (N) fertiliser and employed a machine learning random forest model to test the use of natural abundance stable isotopic N (δ 15 N) to predict site response. Pinus radiata growth response was calculated as the change in periodic annual increment of basal area (PAI BA) from replicated control and treatment (~ 200 kg N ha −1 ) plots within trials across New Zealand. Variables in the analysis were climate, silviculture, soil, and foliage chemical properties, including natural abundance δ 15 N values as integrators of historical patterns in N cycling. Our Random Forest model explained 78% of the variation in growth with tree age and the δ 15 N enrichment factor (δ 15 N foliage − δ 15 N soil ) showing more than 50% relative importance to the model. Tree growth rates generally decreased with more negative δ 15 N enrichment factors. Growth response to N fertiliser was highly variable. If a response was going to occur, it was most likely within 1–3 years after fertiliser addition. The Random Forest model predicts that younger stands (< 15 years old) with the freedom to grow and sites with more negative δ 15 N isotopic enrichment factors will exhibit the biggest growth response to N fertiliser. Supporting the challenge of forest nutrient management, these findings provide a novel decision-support tool to guide the intensification of nutrient additions.

Bona fide upcycling strategy of anhydride cured epoxy and reutilization of decomposed dual monomers into multipurpose applications - Lin Shao; Yu-Chung Chang; Baoming Zhao; Xinyan Yan; Brian J. Bliss; Ming-en Fei; Chenhao Yu; Jinwen Zhang (Chemical Engineering Journal, 2023)

Phylotype resolved spatial variation and association patterns of planktonic Thaumarchaeota in eastern Chinese marginal seas - Jiwen Liu; Fuyan Huang; Jiao Liu; Xiaoyue Liu; Ruiyun Lin; Xiaosong Zhong; Brian Austin; Xiao-Hua Zhang (Marine Life Science & Technology, 2023)
The majority of marine ammonia oxidizers belong to Thaumarchaeota , a phylum of Archaea, which is distributed throughout the water column. Marine surface waters contain distinct thaumarchaeotal phylotypes compared to the deeper ocean, but spatial dynamics of the surface-associated lineages are largely unsolved. This study of 120 seawater samples from the eastern Chinese marginal seas identified contrasting distribution and association patterns among thaumarchaeotal phylotypes across different dimensions. Horizontally, Nitrosopumilus -like and Nitrosopelagicus -like phylotypes dominated the surface water (3 m) of the Yellow Sea (YS) and East China Sea (ECS), respectively, along with increased abundance of total free-living Thaumarchaeota in ECS. Similar compositional changes were observed in the surface microlayer. The spatial heterogeneity of particle-attached Thaumarchaeota was less clear in surface microlayers than in surface waters. Vertically, the Nitrosopelagicus -like phylotype increased in abundance from surface to 90 m in ECS, which led to an increase in the proportion of Thaumarchaeota relative to total prokaryotes. This occurred mainly in the free-living fraction. These results indicate a clear size-fractionated niche partitioning, which is more pronounced at lower depths than in the surface water/surface microlayer. In addition, associations of Thaumarchaeota with other microbial taxa varied between phylotypes and size fractions. Our results show that a phylotype-resolved and size-fractionated spatial heterogeneity of the thaumarchaeotal community is present in surface oceanic waters and a vertical variation of the Nitrosopelagicus -like phylotype is present in shallow shelf waters.

Evaluation of visible spectroscopy and low-field nuclear magnetic resonance techniques for screening the presence of defects in broiler breast fillets - Bin Pang; Brian Bowker; Chang-Hu Xue; Yao-Guang Chang; Jian Zhang; Lin Gao; Hong Zhuang (Food Control, 2023)

Pollen in the Baltic Sea as viewed from space - Chuanmin Hu; Lin Qi; David C. English; Menghua Wang; Karlis Mikelsons; Brian B. Barnes; Magdalena M. Pawlik; Dariusz Ficek (Remote Sensing of Environment, 2023)

High level of somatic mutations detected in a diploid banana wild relative Musa basjoo - Yilun Ji; Xiaonan Chen; Shengqiu Lin; Milton Brian Traw; Dacheng Tian; Sihai Yang; Long Wang; Ju Huang (Molecular Genetics and Genomics, 2023)

Tallo: A global tree allometry and crown architecture database - Tommaso Jucker; Fabian Jörg Fischer; Jérôme Chave; David A. Coomes; John Caspersen; Arshad Ali; Grace Jopaul Loubota Panzou; Ted R. Feldpausch; Daniel Falster; Vladimir A. Usoltsev; Stephen Adu‐Bredu; Luciana F. Alves; et al. (Global Change Biology, 2022)
Data capturing multiple axes of tree size and shape, such as a tree's stem diameter, height and crown size, underpin a wide range of ecological research—from developing and testing theory on forest structure and dynamics, to estimating forest carbon stocks and their uncertainties, and integrating remote sensing imagery into forest monitoring programmes. However, these data can be surprisingly hard to come by, particularly for certain regions of the world and for specific taxonomic groups, posing a real barrier to progress in these fields. To overcome this challenge, we developed the Tallo database, a collection of 498,838 georeferenced and taxonomically standardized records of individual trees for which stem diameter, height and/or crown radius have been measured. These data were collected at 61,856 globally distributed sites, spanning all major forested and non‐forested biomes. The majority of trees in the database are identified to species (88%), and collectively Tallo includes data for 5163 species distributed across 1453 genera and 187 plant families. The database is publicly archived under a CC‐BY 4.0 licence and can be access from: https://doi.org/10.5281/zenodo.6637599 . To demonstrate its value, here we present three case studies that highlight how the Tallo database can be used to address a range of theoretical and applied questions in ecology—from testing the predictions of metabolic scaling theory, to exploring the limits of tree allometric plasticity along environmental gradients and modelling global variation in maximum attainable tree height. In doing so, we provide a key resource for field ecologists, remote sensing researchers and the modelling community working together to better understand the role that trees play in regulating the terrestrial carbon cycle.

Factors associated with changes in exercise behaviors during the COVID-19 pandemic - Caroline Himbert; Cassandra A. Hathaway; Bailee Daniels; Karen Salas; Anjelica Ashworth; Biljana Gigic; Tengda Lin; Richard Viskochil; Anne C. Kirchhoff; Douglas Grossman; Jennifer Ose; Jonathan Tward; et al. (Cancer Causes & Control, 2022)

Genetic dissection of a pericentromeric region of barley chromosome 6H associated with Fusarium head blight resistance, grain protein content and agronomic traits - Yadong Huang; Lu Yin; Ahmad H. Sallam; Shane Heinen; Lin Li; Karen Beaubien; Ruth Dill-Macky; Yanhong Dong; Brian J. Steffenson; Kevin P. Smith; Gary J. Muehlbauer (Theoretical and Applied Genetics, 2021)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Chronic AdipoRon Treatment Mimics the Effects of Physical Exercise on Restoring Hippocampal Neuroplasticity in Diabetic Mice - Thomas H Lee; Ahadullah; Brian R Christie; Kangguang Lin; Parco Ming-fai Siu; Li Zhang; Ti-fei Yuan; Pragya Komal; Aimin Xu; Kwok-fai So; Suk-yu Yau (Molecular Neurobiology, 2021)
Administration of exercise mimetic drugs could be a novel therapeutic approach to combat comorbid neurodegeneration and metabolic syndromes. Adiponectin is an adipocyte-secreted hormone. In addition to its antidiabetic effect, adiponectin mediates the antidepressant effect of physical exercise associated with adult hippocampal neurogenesis. The antidiabetic effect of the adiponectin receptor agonist AdipoRon has been demonstrated, but its potential pro-cognitive and neurotrophic effects in the hippocampus under diabetic condition are still unclear. This study reported that chronic AdipoRon treatment for 2 weeks improved hippocampal-dependent spatial recognition memory in streptozotocin-induced diabetic mice. Besides, AdipoRon treatment increased progenitor cell proliferation and neuronal differentiation in the hippocampal dentate gyrus (DG) of diabetic mice. Furthermore, AdipoRon treatment significantly increased dendritic complexity, spine density, and N -methyl-D-aspartate receptor-dependent long-term potentiation (LTP) in the dentate region, and increased BDNF levels in the DG of diabetic mice. AdipoRon treatment activated AMPK/PGC-1α signalling in the DG, whereas increases in cell proliferation and LTP were not observed when PGC-1α signalling was pharmacologically inhibited. In sum, chronic AdipoRon treatment partially mimics the benefits of physical exercise for learning and memory and hippocampal neuroplasticity in the diabetic brain. The results suggested that AdipoRon could be a potential physical exercise mimetic to improve hippocampal plasticity and hence rescue learning and memory impairment typically associated with diabetes.

Modelling stakeholder satisfaction for conflict resolution in wildlife management: a case of wolf population in Sweden - Huayi Lin; Piotr Żebrowski; Brian D. Fath; Hans Liljenström; Elena Rovenskaya (European Journal of Wildlife Research, 2021)
The Swedish wolf population has rebounded from near extinction in the 1960s to around 365 individuals in 2020, after the implementation of the Hunting Act (jaktlagen) in 1966. This recent increase in the wolf population has evoked a serious divide between “pro-wolf” and “anti-wolf” Swedish citizens. Despite the continuous efforts by the Swedish government to reconcile this antagonism, the conflicts are persistent with a sign of impasse. In this paper, we present a modelling tool, which can bring transparent and “structured dialogue to the opposing positions.” This approach includes a stylized framework for quantitative modelling of stakeholders’ satisfaction levels regarding their preferred size of the wildlife population in question, based on the concept of satisfaction functions . We argue that this framework may contribute to conflict resolution by bringing a common understanding among stakeholders, facilitate a societal discourse, and potentially help to assess likely support for conservation policies. We present a showcase application of this modeling tool in the context of the conflict over the Swedish wolf conservation policies. The model is informed using a thorough literature review as well as interviews, which identified relevant stakeholder groups and respective drivers of their attitudes towards wolves.

The ENIGMA sports injury working group:– an international collaboration to further our understanding of sport-related brain injury - Inga K. Koerte; Carrie Esopenko; Sidney R. Hinds; Martha E. Shenton; Elena M. Bonke; Jeffrey J. Bazarian; Kevin C. Bickart; Erin D. Bigler; Sylvain Bouix; Thomas A. Buckley; Meeryo C. Choe; Paul S. Echlin; et al. (Brain Imaging and Behavior, 2021)
Sport-related brain injury is very common, and the potential long-term effects include a wide range of neurological and psychiatric symptoms, and potentially neurodegeneration. Around the globe, researchers are conducting neuroimaging studies on primarily homogenous samples of athletes. However, neuroimaging studies are expensive and time consuming, and thus current findings from studies of sport-related brain injury are often limited by small sample sizes. Further, current studies apply a variety of neuroimaging techniques and analysis tools which limit comparability among studies. The ENIGMA Sports Injury working group aims to provide a platform for data sharing and collaborative data analysis thereby leveraging existing data and expertise. By harmonizing data from a large number of studies from around the globe, we will work towards reproducibility of previously published findings and towards addressing important research questions with regard to diagnosis, prognosis, and efficacy of treatment for sport-related brain injury. Moreover, the ENIGMA Sports Injury working group is committed to providing recommendations for future prospective data acquisition to enhance data quality and scientific rigor.

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

A generic brain connectome map linked to different types of everyday decision-making in old age - Brian Rooks; Mia Anthony; Quanjing Chen; Ying Lin; Timothy Baran; Zhengwu Zhang; Peter A. Lichtenberg; Feng Lin (Brain Structure and Function, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Storm surge return levels induced by mid-to-late-twenty-first-century extratropical cyclones in the Northeastern United States - Ning Lin; Reza Marsooli; Brian A. Colle (Climatic Change, 2019)

Significance of Vibrio species in the marine organic carbon cycle—A review - Xiaohua Zhang; Heyu Lin; Xiaolei Wang; Brian Austin (Science China Earth Sciences, 2018)

The Benefits of Reduced Anthropogenic Climate changE (BRACE): a synthesis - Brian C. O’Neill; James M. Done; Andrew Gettelman; Peter Lawrence; Flavio Lehner; Jean-Francois Lamarque; Lei Lin; Andrew J. Monaghan; Keith Oleson; Xiaolin Ren; Benjamin M. Sanderson; Claudia Tebaldi; et al. (Climatic Change, 2018)

The role of functional uniqueness and spatial aggregation in explaining rarity in trees - María Natalia Umaña; Xiangcheng Mi; Min Cao; Brian J. Enquist; Zhanqing Hao; Robert Howe; Yoshiko Iida; Daniel Johnson; Luxiang Lin; Xiaojuan Liu; Keping Ma; I‐Fang Sun; et al. (Global Ecology and Biogeography, 2017)
Aim Determining the drivers of species rarity is fundamental for understanding and conserving biodiversity. Rarity of a given species within its community may arise due to exclusion by other ecologically similar species. Conversely, rare species may occupy habitats that are rare in the landscape or they may be ill‐suited to all available habitats. The first mechanism would lead to common and rare species occupying similar ecological space defined by functional traits. The second mechanism would result in common and rare species occupying dissimilar ecological space and spatial aggregation of rare species, either because they are specialists in rare habitats or because rare species tend to be dispersal limited. Here, we quantified the contribution of locally rare species to community functional richness and the spatial aggregation of species across tree communities world‐wide to address these hypotheses. Location Asia and the Americas. Time period 2002 to 2012 (period that considers the censuses for the plots used). Major taxa studied Angiosperm and Gymnosperm trees. Methods We compiled a dataset of functional traits from all the species present in eight tree plots around the world to evaluate the contribution of locally rare species to tree community functional richness using multi‐ and univariate approaches. We also quantified the spatial aggregation of individuals within species at several spatial scales as it relates to abundance. Results Locally rare tree species in temperate and tropical forests tended to be functionally unique and are consistently spatially clustered. Furthermore, there is no evidence that this pattern is driven by pioneer species being locally rare. Main conclusions This evidence shows that locally rare tree species disproportionately contribute to community functional richness, and we can therefore reject the hypothesis that locally rare species are suppressed by ecologically similar, but numerically dominant, species. Rather, locally rare species are likely to be specialists on spatially rare habitats or they may be ill‐suited to the locally available environments.

Chromogenic media for MRSA diagnostics - Zhenbo Xu; Yuchao Hou; Brian M. Peters; Dingqiang Chen; Bing Li; Lin Li; Mark E. Shirtliff (Molecular Biology Reports, 2016)

Developing Single Nucleotide Polymorphism (SNP) Markers for the Identification of Coffee Germplasm - Lin Zhou; Fernando E. Vega; Huawei Tan; Aixa E. Ramírez Lluch; Lyndel W. Meinhardt; Wanping Fang; Sue Mischke; Brian Irish; Dapeng Zhang (Tropical Plant Biology, 2016)

Biogeographic patterns of soil diazotrophic communities across six forests in the North America - Qichao Tu; Ye Deng; Qingyun Yan; Lina Shen; Lu Lin; Zhili He; Liyou Wu; Joy D. Van Nostrand; Vanessa Buzzard; Sean T. Michaletz; Brian J. Enquist; Michael D. Weiser; et al. (Molecular Ecology, 2016)
Soil diazotrophs play important roles in ecosystem functioning by converting atmospheric N 2 into biologically available ammonium. However, the diversity and distribution of soil diazotrophic communities in different forests and whether they follow biogeographic patterns similar to macroorganisms still remain unclear. By sequencing nifH gene amplicons, we surveyed the diversity, structure and biogeographic patterns of soil diazotrophic communities across six North American forests (126 nested samples). Our results showed that each forest harboured markedly different soil diazotrophic communities and that these communities followed traditional biogeographic patterns similar to plant and animal communities, including the taxa–area relationship ( TAR ) and latitudinal diversity gradient. Significantly higher community diversity and lower microbial spatial turnover rates (i.e. z ‐values) were found for rainforests (~0.06) than temperate forests (~0.1). The gradient pattern of TAR s and community diversity was strongly correlated ( r 2 > 0.5) with latitude, annual mean temperature, plant species richness and precipitation, and weakly correlated ( r 2 pH and soil moisture. This study suggests that even microbial subcommunities (e.g. soil diazotrophs) follow general biogeographic patterns (e.g. TAR , latitudinal diversity gradient), and indicates that the metabolic theory of ecology and habitat heterogeneity may be the major underlying ecological mechanisms shaping the biogeographic patterns of soil diazotrophic communities.

Poly(lactic-co-glycolide) polymer constructs cross-linked with human BMP-6 and VEGF protein significantly enhance rat mandible defect repair - Anusuya Das; Brian A. Fishero; J. Jared Christophel; Ching-Ju Li; Nikita Kohli; Yong Lin; Abhijit S. Dighe; Quanjun Cui (Cell and Tissue Research, 2016)

Fully automatic and nonparametric quantification of adipose tissue in fat–water separation MR imaging - Defeng Wang; Lin Shi; Winnie C. W. Chu; Miao Hu; Brian Tomlinson; Wen-Hua Huang; Tianfu Wang; Pheng Ann Heng; David K. W. Yeung; Anil T. Ahuja (Medical & Biological Engineering & Computing, 2015)

The most frequent interfaces in olivine aggregates: the GBCD and its importance for grain boundary related processes - Katharina Marquardt; Gregory S. Rohrer; Luiz Morales; Erik Rybacki; Hauke Marquardt; Brian Lin (Contributions to Mineralogy and Petrology, 2015)

Prediction and validation of enzyme and transporter off-targets for metformin - Sook Wah Yee; Lawrence Lin; Matthew Merski; Michael J. Keiser; Aakash Gupta; Youcai Zhang; Huan-Chieh Chien; Brian K. Shoichet; Kathleen M. Giacomini (Journal of Pharmacokinetics and Pharmacodynamics, 2015)

Advanced neuroimaging applied to veterans and service personnel with traumatic brain injury: state of the art and potential benefits - Elisabeth A. Wilde; Sylvain Bouix; David F. Tate; Alexander P. Lin; Mary R. Newsome; Brian A. Taylor; James R. Stone; James Montier; Samuel E. Gandy; Brian Biekman; Martha E. Shenton; Gerald York (Brain Imaging and Behavior, 2015)

Interactive effects of light, nitrogen source, and carbon dioxide on energy metabolism in the diatom Thalassiosira pseudonana - Dalin Shi; Weiying Li; Brian M. Hopkinson; Haizheng Hong; Dongmei Li; Shuh‐Ji Kao; Wenfang Lin (Limnology and Oceanography, 2015)
Due to the ongoing effects of climate change, phytoplankton are likely to experience enhanced irradiance, more reduced nitrogen, and increased water acidity in the future ocean. Here, we used Thalassiosira pseudonana as a model organism to examine how phytoplankton adjust energy production and expenditure to cope with these multiple, interrelated environmental factors. Following acclimation to a matrix of irradiance, nitrogen source, and CO 2 levels, the diatom's energy production and expenditures were quantified and incorporated into an energetic budget to predict how photosynthesis was affected by growth conditions. Increased light intensity and a shift from to led to increased energy generation, through higher rates of light capture at high light and greater investment in photosynthetic proteins when grown on . Secondary energetic expenditures were adjusted modestly at different culture conditions, except that utilization was systematically reduced by increasing p CO 2 . The subsequent changes in element stoichiometry, biochemical composition, and release of dissolved organic compounds may have important implications for marine biogeochemical cycles. The predicted effects of changing environmental conditions on photosynthesis, made using an energetic budget, were in good agreement with observations at low light, when energy is clearly limiting, but the energetic budget over‐predicts the response to at high light, which might be due to relief of energetic limitations and/or increased percentage of inactive photosystem II at high light. Taken together, our study demonstrates that energetic budgets offered significant insight into the response of phytoplankton energy metabolism to the changing environment and did a reasonable job predicting them.

Migratory history of African longfinned eel Anguilla mossambica from Maningory River, Madagascar: discovery of a unique pattern in otolith Sr:Ca ratios - Yu-Jia Lin; Brian M. Jessop; Olaf L. F. Weyl; Yoshiyuki Iizuka; Shih-Huan Lin; Wann-Nian Tzeng (Environmental Biology of Fishes, 2015)

Responsiveness of cardiometabolic-related microbiota to diet is influenced by host genetics - Annalouise O’Connor; Pamela M. Quizon; Jody E. Albright; Fred T. Lin; Brian J. Bennett (Mammalian Genome, 2014)

A new modified sesquiterpene glycoside from Cupressus chengiana - Yan Lin; Rong-Jiao Li; Yan Li; Brian D. McGarvey; Hai-Feng Wu; Xiao-Ling Wang (Natural Product Research, 2014)

The California Breast Cancer Survivorship Consortium (CBCSC): prognostic factors associated with racial/ethnic differences in breast cancer survival - Anna H. Wu; Scarlett Lin Gomez; Cheryl Vigen; Marilyn L. Kwan; Theresa H. M. Keegan; Yani Lu; Salma Shariff-Marco; Kristine R. Monroe; Allison W. Kurian; Iona Cheng; Bette J. Caan; Valerie S. Lee; et al. (Cancer Causes & Control, 2013)

Feasibility Study on Quantitative Measurements of Singlet Oxygen Generation Using Singlet Oxygen Sensor Green - Huiyun Lin; Yi Shen; Defu Chen; Lisheng Lin; Brian C. Wilson; Buhong Li; Shusen Xie (Journal of Fluorescence, 2013)

Otolith Sr:Ca and Ba:Ca may give inconsistent indications of estuarine habitat use for American eels (Anguilla rostrata) - Brian M. Jessop; Chia-Hui Wang; Wann-Nian Tzeng; Chen-Feng You; Jen-Chieh Shiao; Shih-Huan Lin (Environmental Biology of Fishes, 2012)

The Business of Forest Enterprise / Urban Ecosystems / Forest Policy / Biosecurity - David Nicholls; Allen Brackley; Charles Keegan; Colin Sorenson; Jean Daniels; Erik Berg; Charles Gale; Robert Campbell; Charles Gale; Charles Keegan; Erik Berg; Colin Sorenson; et al. (Journal of Forestry, 2011)
172Business clusters are geographic concentrations of companies that provide mutual advantages for their participants. Clusters can include diverse members including competitors, customers, partners, and/or suppliers. In Alaska, wood products business clusters can have unique challenges associated with remote locations, high raw material costs, limited local markets, and potentially long transportation distances. Further, multiple land ownership near communities (for example state versus federal ownership) can influence raw material procurement, since different administrative processes for timber harvesting may be required. This study evaluates 2 resource dependent communities in southeast Alaska (Haines, AK and Craig, AK), seeking to identify elements that could enhance their potential for wood products clusters and new business formation. We consider how the flow of forest resources, from harvest to finished product, can influence local communities and either enhance or limit opportunities for wood products businesses. We evaluate the effect of various product mixes—including firewood, woody residues, house logs, lumber, and secondary wood products—on the composition, scale, and dynamics of wood products firms. We consider the effect of harvesting practices and proximity to timber sales in evaluating how land ownership can influence the viability of wood products clusters. Lastly we consider the impact of transportation costs on serving local and export markets. Our research builds upon past work in Alaska that evaluated national-forest based communities in Alaska, finding opportunities for greater innovation, higher productivity, and greater social well-being associated with wood products clusters.

Pig transgenesis by Sleeping Beauty DNA transposition - Jannik E. Jakobsen; Juan Li; Peter M. Kragh; Brian Moldt; Lin Lin; Ying Liu; Mette Schmidt; Kjeld Dahl Winther; Brian Dall Schyth; Ida E. Holm; Gábor Vajta; Lars Bolund; et al. (Transgenic Research, 2011)

Perceptions of Colorectal Cancer Screening in Urban African American Clinic Patients: Differences by Gender and Screening Status - Sarah Bauerle Bass; Thomas F. Gordon; Sheryl Burt Ruzek; Caitlin Wolak; Stephanie Ward; Anuradha Paranjape; Karen Lin; Brian Meyer; Dominique G. Ruggieri (Journal of Cancer Education, 2011)

Functional evaluation of therapeutic response for a mouse model of medulloblastoma - Aislynn K. Samano; Sachiko Ohshima-Hosoyama; Thomas G. Whitney; Suresh I. Prajapati; Aoife Kilcoyne; Eri Taniguchi; William W. Morgan; Laura D. Nelon; Ai-Ling Lin; Osamu Togao; Inkyung Jung; Brian P. Rubin; et al. (Transgenic Research, 2010)

Angiotensin IV elevates oxytocin levels in the rat amygdala and produces anxiolytic-like activity through subsequent oxytocin receptor activation - Chad E. Beyer; Jason M. Dwyer; Brian J. Platt; Sarah Neal; Bin Luo; Huai-Ping Ling; Qian Lin; Robert J. Mark; Sharon Rosenzweig-Lipson; Lee E. Schechter (Psychopharmacology, 2010)

Sorption of the herbicide terbuthylazine in two New Zealand forest soils amended with biosolids and biochars - Hailong Wang; Kunde Lin; Zhenan Hou; Brian Richardson; Jay Gan (Journal of Soils and Sediments, 2010)

Loss of apical monocilia on collecting duct principal cells impairs ATP secretion across the apical cell surface and ATP-dependent and flow-induced calcium signals - Michael B. Hovater; Dragos Olteanu; Elizabeth L. Hanson; Nai-Lin Cheng; Brian Siroky; Attila Fintha; Peter Komlosi; Wen Liu; Lisa M. Satlin; P. Darwin Bell; Bradley K. Yoder; Erik M. Schwiebert (Purinergic Signalling, 2008)

Evaluation of a new sitting concept designed for prevention of pressure ulcer on the buttock using finite element analysis - Dohyung Lim; Fang Lin; Ronald W. Hendrix; Brian Moran; Charles Fasanati; Mohsen Makhsous (Medical & Biological Engineering & Computing, 2007)

Embedded together: The life and death consequences of interaction of the Bcl-2 family with membranes - Brian Leber; Jialing Lin; David W. Andrews (Apoptosis, 2007)

Multidisciplinary Approaches to Natural Resource Management - Terry Hillman; Lin Crase; Brian Furze; Jayanath Ananda; Daryl Maybery (Hydrobiologia, 2005)

Peptide mimotopes of phomopsins: Identification, characterization and application in an immunoassay - Meng Yu; Khin Than; Steve Colegate; Brian Shiell; Wojtek P. Michalski; Stephen Prowse; Lin-Fa Wang (Molecular Diversity, 2005)

Precipitation from vertical motion: a statistical diagnostic scheme - Brian E. J. Rose; Charles A. Lin (International Journal of Climatology, 2003)
The relationship between precipitation and atmospheric vertical motion is investigated over the globe. By combining and averaging precipitation rates within small ranges of vertical motion, the mean precipitation rate is found to vary smoothly with vertical motion. The relationship is modelled with a simple function that assumes zero precipitation for subsidence and linearly increasing precipitation for ascending motion. Function parameters are computed from National Centers for Environmental Prediction reanalysis data individually for every grid point and calendar month. Variations in the slope account for geographical and seasonal variations in moisture and other precipitation factors. At each grid point, the scheme diagnoses precipitation rate from a single concurrent value of vertical motion. It is shown to have moderate skill over climatology in predicting mean monthly precipitation. The midlatitudes, oceans and the winter season are favoured. The scheme is designed to extract precipitation fields from a dry general circulation model, based on the simulated vertical motion. Application to climate modelling is discussed. Copyright © 2003 Royal Meteorological Society

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Pharmacokinetics and Biologic Activity of the Novel Mast Cell Inhibitor, 4-(3′-Hydroxyphenyl)-amino-6,7-dimethoxyquinazoline in Mice - Chun-Lin Chen; Ravi Malaviya; Christopher Navara; Hao Chen; Brian Bechard; Greg Mitcheltree; Xing-Ping Liu; Fatih M. Uckun (Pharmaceutical Research, 1999)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)